The impact of governance on economic growth in Malaysia - Huang, Chiung-Ju; Ho, Yuan-Hong (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2021)
This study uses the Autoregressive Distributed Lag (ARDL) model to examine the effect of governance on economic growth in Malaysia over the 1996 to 2018 period. In this study the standard of governance is graded as democratic and scientific. These two global governance metrics are synonymous with “voice and accountability” and “political stability and absence of violence” (WGIs). In the meantime, four WGI metrics are concerned with “government effectiveness”, “regulatory quality”, “rule of law”, and “control of corruption”. Empirical results show that the impact of democratic quality and technical quality on economic growth is significantly positive. The findings suggest that the promotion of good governance is useful in facilitating economic growth in Malaysia.